An iterative method for solving the dynamic response of railway vehicle-track coupled systems based on prediction of wheel-rail forces. (15th November 2017) - Wang, Wei; Zhang, Yahui; Ouyang, Huajiang
Highlights: An iterative method based on prediction of wheel-rail forces is presented. The Weighted Least-Squares Error (WLSE) predictor is introduced. The wheel-rail interaction model considers detailed wheel rail contact relations. The accuracy of the presented method is verified by comparing with NUCARS. Abstract: An iterative method based on prediction of wheel-rail forces is presented to determine the dynamic response of railway vehicle-track coupled systems. The key idea of the present method lies in the modification of the starting value of each step during the iteration by prediction. The conventional iterative method begins iteration of the current step at the previously converged value of the wheel-rail forces. However, in the present method, the predicted wheel-rail forces by the Weighted Least-Squares Error (WLSE) predictor are used as the starting value for the current step. The equations of motion of the vehicle and the track subsystems are established separately and solved iteratively. According to the response of the wheelsets and the rails, and considering the track irregularity, the predicted wheel-rail forces are corrected by the wheel-rail interaction model in which detailed wheel rail contact geometry relations and nonlinear wheel rail creep forces are taken into account. The relaxation technique is adopted to solve the problem of numerical diffusion in the iterative process. A moving vehicle travelling on a two layer flexible track is considered in this study. The accuracy of the proposed method is verified by comparing the results obtained from the present method with the results from the commercial software NUCARS and the efficiency are verified by comparing with the conventional iterative method. Numerical results show that the present method not only gives results comparable to those using the NUCARS software in terms of accuracy, but also saves at least 25% computational cost compared with the conventional iterative method. With the nonlinear wheel-rail contact relation fully considered, the present method can get more detailed results of the vehicle-track coupled model. Meanwhile, the efficiency of the present method is enhanced by means of prediction of wheel-rail forces with the WLSE predictor.